Sarcopenia reduces overall survival in unresectable oesophageal cancer: a systematic review and meta‐analysis. Issue 6 (24th September 2022) - Jogiat, Uzair M.; Bédard, Eric L.R.; Sasewich, Hannah; Turner, Simon R.; Eurich, Dean T.; Filafilo, Heather; Baracos, Vickie
Abstract: Sarcopenia measured through body composition analysis is emerging as an important prognosticator among various malignancies, including oesophageal cancer. Skeletal muscle index (SMI) as determined by the third lumbar vertebrae on cross‐sectional CT images has been demonstrated as a predictor of overall survival in oesophageal cancer, using pre‐defined cut off values for sarcopenia. However, this is largely within the setting of resectable disease. The primary objective of this systematic review and meta‐analysis was to determine the effect of sarcopenia defined by SMI on overall‐survival in patients with unresectable oesophageal cancer. On 30 January 2021, a systematic search of the literature was conducted to identify the role of SMI among patients with unresectable oesophageal cancer, with overall survival as the primary outcome. Databases included MEDLINE, EMBASE, Scopus, Web of Science, and Cochrane Library. Inclusion criteria included age >18, diagnosis of oesophageal cancer, and non‐operative management. A meta‐analysis was conducted using RevMan 5.4.1 using an inverse variance, random effects model. After the removal of duplicates, 2755 unique search results were obtained. Manual screening of titles and abstracts resulted in 287 full text articles that were reviewed. Of these, five studies met the inclusion criteria with data evaluating the effect of sarcopenia defined by SMI on overall survival. A total of 783 patients, the majority of which were male ( n  = 638, 81%), with a mean age of 68 ± 2.3 years were included. 641 (82%) patients were diagnosed with squamous cell carcinoma. Sarcopenia, as determined by SMI using pre‐defined cut‐off values, was reported in 517 patients (66%). Meta‐analysis demonstrated decreased overall survival in the sarcopenia group compared with the non‐sarcopenia group (HR = 1.51; 95% CI 1.21–1.89; P  = 0.0003; I 2  = 0%; Figure 1). No significant publication bias was noted on assessment of funnel plot and Egger's test ( P  = 0.295). Sarcopenia as defined by SMI is predictive of overall survival among patients with nonoperative oesophageal cancer. Further analysis on the effect of sarcopenia on treatment related adverse effects and complications, particularly related to chemotherapy, radiotherapy, and oesophageal stenting, is needed to identify the degree of prognostication offered by body composition analysis. Studies on the modifiability of sarcopenia will help determine the utility of nutritional interventions.